2008
DOI: 10.1063/1.2829803
|View full text |Cite
|
Sign up to set email alerts
|

Interface mixing of Al∕Fe and Fe∕Al bilayer systems and the role of Ti as a stabilizing interlayer using Rutherford backscattering spectrometry and x-ray reflectometry

Abstract: Al ∕ Fe and Fe∕Al bilayer films with and without a Ti stabilizing interlayer at the interface have been grown on Si wafers using dc magnetron sputtering. X-ray reflectometry and Rutherford backscattering spectrometry were used to probe individual layer thicknesses and intermixing lengths. It is observed that the intermixing length is always higher when the Fe layer is on top of the Al layer. The samples with the Ti stabilizing layer, particularly when the Al layer is on top of the Fe, show that the Ti layer pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…49,50,57 The kinetics of intermixing are characterized by the irradiation dose dependence of the intermixing length squared, X 2 , according to the "compound formation model". 58,59 On this basis, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…49,50,57 The kinetics of intermixing are characterized by the irradiation dose dependence of the intermixing length squared, X 2 , according to the "compound formation model". 58,59 On this basis, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This tail was too large to be caused by double or plural scattering and the surface roughness was also too small to explain this phenomenon. Recently, similar asymmetry was found on Fe/Al versus Al/Fe bilayers, which elements are also immiscible [12].…”
Section: Introductionmentioning
confidence: 52%
“…27 In previous work we described an approach to stabilize the Fe-Al interface using a thin Ti͑ϳ15 Å͒ layer to reduce intermixing between Fe-Al at the interface. 13 In this work we test the stability of the Fe-Al interface with other stabilizing elements, namely V and Zr, and also test the effectiveness of extremely thin Ti interlayers ͑ϳ3 Å͒ for stabilizing the Fe-Al interface in sputtered polycrystalline films. Figure 4 shows the XRR specular scans and BEDE simulations of the Fe-Al interface with 3 Å thick Ti, 9 Å thick V, and 6 Å thick Zr interface stabilizing layers.…”
Section: Resultsmentioning
confidence: 99%
“…We reported that a thin Ti layer can be used to stabilize sputter deposited Fe-Al polycrystalline thin films grown on SiO 2 / Si wafers. 13 Model calculations using BFS quantum approximate methods were performed to identify other potential stabilizing layers for the Fe-Al system, and the results indicated that both Ti and V might be effective in this role. 14 We also decided to test Zr as an interlayer between Fe and Al because Ti and Zr have many chemical and physical similarities, but our model calculations did not predict that Zr would be effective as a stabilizing interlayer between Fe and Al.…”
Section: Introductionmentioning
confidence: 99%